Investigating the detection of underground nuclear explosions by radon displacement. (April 2021) - Burnett, Jonathan L.; Stewart, Timothy L.; Keillor, Martin E.; Ely, James H.
Abstract: A novel approach is proposed to detect underground nuclear explosions (UNEs) through the displacement of natural radon isotopes ( 222 Rn and 220 Rn). Following an explosion, it is hypothesized that the disturbance and pressurization of the sub-surface would facilitate the movement of radon from the depth of the UNE towards the surface resulting in increased soil gas activity. The resulting signal may be magnified by a factor of 2.0–4.9 by the decay of radon to its short-lived progeny. Increases in background activity may be useful for identifying locations to perform additional measurements, or as a detectable signal at monitoring stations. To validate this hypothesis, radon detection instrumentation was deployed at the Dry Alluvium Geology (DAG) site of the Source Physics Experiment (SPE) at the Nevada National Security Site (NNSS). Natural fluctuations in the soil gas activity due to barometric pumping, and the lower yield of the chemical explosions (1–50 t) made it difficult to confirm a displacement of radon from the explosions, and further study to validate the proposed hypothesis is recommended. Highlights: A novel approach is proposed to detect underground nuclear explosions through the displacement of natural radon isotopes It is hypothesized that the disturbance and pressurization from the explosion would facilitate the movement of radon towards the surface The signal may be magnified by the decay of radon to its short-lived progeny The elevated background activity may be useful for identifying locations to perform additional measurements, or as a detectable signal at monitoring stations The hypothesis was investigated with radon measurements at the Dry Alluvium Geology site of the Source Physics Experiment